Novel roller screening technology for enhanced reduction of fine particles in iron ore fired pellets production - Alexandre Gonçalves Andrade; Steve Beaudin; Eric Tremblay; François Cloutier-Poirier; Hilcker Scopel Damasceno; Luiz Carlos Gavazza Junior; Lukas Dion; Patrick Faubert (Minerals Engineering, 2026)

Species-specific responses of boreal conifer seedlings to nitrogen availability: effects on growth, biomass partitioning, bud production and root traits - Charles Marty; Ranieri Ribeiro Paula; Lona Baudry; Olivier Fradette; Patrick Faubert (Trees, 2026)

Conventional and industrial by-product fertilization do not induce greenhouse gas emissions in sandy soils under wild lowbush blueberry cropping in eastern Canada - Anthony J. Pelletier; Patrick Faubert; Jean Lafond; Normand Bertrand; Jean Legault; Rock Ouimet; David E. Pelster; André Pichette; Noura Ziadi; Maxime C. Paré (Geoderma Regional, 2025)

Correction factors for large-scale greenhouse gas assessment from pulp and paper mill sludge landfill sites - Ranieri Ribeiro Paula; Mathieu Cusson; Normand Bertrand; Sylvie Bouchard; Martin H. Chantigny; Julie Lemieux; Emna Marouani; Claude Villeneuve; Patrick Faubert (Waste Management, 2024)

Assessing soil carbon dynamics following mechanical site preparation in boreal lichen woodlands of Québec, Canada - Charles Marty; Rock Ouimet; Olivier Fradette; Maxime Paré; Patrick Faubert; Claude Villeneuve (Forest Ecology and Management, 2024)

Performance of seedlings of four coniferous species planted in two boreal lichen woodlands with contrasting soil fertility - Charles Marty; Olivier Fradette; Patrick Faubert; Sylvie Bouchard; Claude Villeneuve (Forest Ecology and Management, 2023)

Climate change‐induced vegetation change as a driver of increased subarctic biogenic volatile organic compound emissions - Hanna Valolahti; Minna Kivimäenpää; Patrick Faubert; Anders Michelsen; Riikka Rinnan (Global Change Biology, 2015)
Emissions of biogenic volatile organic compounds ( BVOC s) have been earlier shown to be highly temperature sensitive in subarctic ecosystems. As these ecosystems experience rapidly advancing pronounced climate warming, we aimed to investigate how warming affects the BVOC emissions in the long term (up to 13 treatment years). We also aimed to assess whether the increased litterfall resulting from the vegetation changes in the warming subarctic would affect the emissions. The study was conducted in a field experiment with factorial open‐top chamber warming and annual litter addition treatments on subarctic heath in Abisko, northern Sweden. After 11 and 13 treatment years, BVOC s were sampled from plant communities in the experimental plots using a push–pull enclosure technique and collection into adsorbent cartridges during the growing season and analyzed with gas chromatography–mass spectrometry. Plant species coverage in the plots was analyzed by the point intercept method. Warming by 2 °C caused a 2‐fold increase in monoterpene and 5‐fold increase in sesquiterpene emissions, averaged over all measurements. When the momentary effect of temperature was diminished by standardization of emissions to a fixed temperature, warming still had a significant effect suggesting that emissions were also indirectly increased. This indirect increase appeared to result from increased plant coverage and changes in vegetation composition. The litter addition treatment also caused significant increases in the emission rates of some BVOC groups, especially when combined with warming. The combined treatment had both the largest vegetation changes and the highest BVOC emissions. The increased emissions under litter addition were probably a result of a changed vegetation composition due to alleviated nutrient limitation and stimulated microbial production of BVOC s. We suggest that the changes in the subarctic vegetation composition induced by climate warming will be the major factor indirectly affecting the BVOC emission potentials and composition.

Biogenic volatile organic compound emissions in four vegetation types in high arctic Greenland - Michelle Schollert; Sebrina Burchard; Patrick Faubert; Anders Michelsen; Riikka Rinnan (Polar Biology, 2014)

The shift in plant species composition in a subarctic mountain birch forest floor due to climate change would modify the biogenic volatile organic compound emission profile - Patrick Faubert; Päivi Tiiva; Anders Michelsen; Åsmund Rinnan; Helge Ro-Poulsen; Riikka Rinnan (Plant and Soil, 2012)

Non-Methane Biogenic Volatile Organic Compound Emissions from a Subarctic Peatland Under Enhanced UV-B Radiation - Patrick Faubert; Päivi Tiiva; Åsmund Rinnan; Janne Räsänen; Jarmo K. Holopainen; Toini Holopainen; Esko Kyrö; Riikka Rinnan (Ecosystems, 2010)